2020
DOI: 10.1097/opx.0000000000001467
|View full text |Cite
|
Sign up to set email alerts
|

Obstructive Sleep Apnea and Keratoconus: A Systematic Review and Meta-analysis

Abstract: BACKGROUND Despite the increasing number of studies focused on the association between obstructive sleep apnea (OSA) and keratoconus (KC), to date, no comprehensive meta-analysis or systematic review was published. OBJECTIVE The objective of this study was to evaluate the association between OSA and KC. DATA SOURCES Sources of data were PubMed, Scopus, and Web of Science databases. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
14
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 52 publications
1
14
0
2
Order By: Relevance
“…In recent years, the relationship between KC and OSA has been increasingly studied, showing inconsistent results. A meta-analysis of one cohort and four case–control studies showed a significant association between KC and OSA (pooled OR: 1.841, p = 0.009) [ 107 ]. See et al conducted a nationwide population-based matched case–control study and found no significant association between KC and SA [ 108 ].…”
Section: Osa-associated Complications In Anterior Segment Of Eyementioning
confidence: 99%
“…In recent years, the relationship between KC and OSA has been increasingly studied, showing inconsistent results. A meta-analysis of one cohort and four case–control studies showed a significant association between KC and OSA (pooled OR: 1.841, p = 0.009) [ 107 ]. See et al conducted a nationwide population-based matched case–control study and found no significant association between KC and SA [ 108 ].…”
Section: Osa-associated Complications In Anterior Segment Of Eyementioning
confidence: 99%
“…Clinically, ocular neuropathic manifestations of OSA include non-arteritic anterior ischemic optic neuropathy, papilledema, and glaucoma [ 11 14 ]. Apart from optic nerve pathology, OSA is associated with keratoconus and floppy eyelid syndrome [ 15 18 ]. Despite corrective surgery for floppy eyelid syndrome, clinical observations suggest that the ocular surface remains abnormal.…”
Section: Introductionmentioning
confidence: 99%
“… 13 Simultaneously, OSA has been found to be associated with various ophthalmic diseases that include glaucoma, 14 , 15 floppy eyelid syndrome, 16 optic neuropathy, 17 , 18 and keratoconus. 19 , 20 …”
mentioning
confidence: 99%